Metode Pembelajaran Manajemen SDM Berbasis Digital Di Gerakan Nasional Indonesia Kompeten (Lembaga Pengembangan Kinerja Dosen, 2025)
In the current era of globalization and digitalization, almost all aspects of life such as business, education, and entertainment have been connected with digital technology, this transformation facilitates access to information and creates various new innovations in many fields. Gerakan Nasional Indonesia Kompeten (GNIK) actively builds collaboration and communication with all human resource practitioners and is an initiative in producing students who have an understanding in the field of human resources in Indonesia. The research method used in writing this report is qualitative with a descriptive approach because the data used for task completion is obtained through interviews and then explained the results obtained through these interviews. Asynchronous learning system is a learning model that allows students to access learning materials and complete learning activities without having to be physically present at the same time as the instructor. Synchronous learning method is learning that involves direct interaction between participants and presenters at the same time in both physical classrooms and digital platforms. The learning methods carried out in Gerakan Nasional Indonesia Kompeten (GNIK), namely syncronus and asyncronus, are related to each other because synchronous provides direct interaction and real-time reinforcement of material while asynchronous provides flexibility for learning according to the time they have and provide more independent learning opportunities.